Caracterização estrutural químico, propriedades reológicas e efeito antioxidante do polissacarídeo sulfatado da alga marinha Acanthophora spicifera - Pereira Júnior, Lindauro da Costa (2018)
Red seaweeds are a natural source of various bioactive compounds, especially carbohydrates. Among these polymers, sulphated polysaccharides are complex molecules that have aroused great interest in the food, pharmaceutical and biotechnology area. Therefore, the study aimed to isolate the sulphated polysaccharide from the red sea kelp Acanthophora spicifera (PS) and to verify its rheological properties and its antioxidant effect. The PS had a mean molar mass of 364 kDa and a carbohydrate content of 75.3%. In addition, the microanalysis showed levels of carbon (23.76%), hydrogen (4.95%), sulfur (6.48%). The chemical characterization of PS was performed by Fourier Transform Infrared Spectroscopy (FTIR) and Nuclear Magnetic Resonance (NMR), identifying PS as a sulfated galactan of the agarana type. Experiments to evaluate the rheological properties of aqueous solutions of the sulphated polysaccharide under study were performed at 25 ± 1 ° C using stationary and dynamic measurements as a thickening agent. The sulfated polysaccharide presented considerable antioxidant activity in all the tests performed with results of 30.29%, 53.48%, 48.27% against the radical DPPH, on the chelation of iron ionsand total antioxidant capacity, respectively. The results suggest the sulphated polysaccharide of Acanthophora spicifera with thickening capacity applied in food production and natural antioxidant potential.